2011
DOI: 10.1542/peds.2010-0929
|View full text |Cite
|
Sign up to set email alerts
|

Serum Transaminase Levels in Boys With Duchenne and Becker Muscular Dystrophy

Abstract: By recognizing muscle as a potential source of serum transaminase levels, clinicians can avoid unnecessary and invasive procedures, expedite clinical diagnosis, and avoid unnecessary cessation of concomitant drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 13 publications
2
54
1
7
Order By: Relevance
“…Findings in humans and in animal models point to disruption of the sarcolemma as a main cause of neuromuscular disease (Mendell et al 1995;Straub et al 1997). Consistent with this, patients affected by Duchenne type neuromuscular dystrophy exhibit increased plasma levels of some muscle fiber content, including enzymes (McMillan et al 2011) and growth factors (D'Amore et al 1994). Of note with respect to our findings, it has been reported that patients affected by painful neuromuscular diseases such as polymyositis and Duchenne type neuromuscular dystrophy exhibit increased expression of GDNF in regenerating muscle fibers (Suzuki et al 1998a).…”
Section: Fig 2 Gdnf Produces Mechanical Hyperalgesia and Sensitizesmentioning
confidence: 61%
“…Findings in humans and in animal models point to disruption of the sarcolemma as a main cause of neuromuscular disease (Mendell et al 1995;Straub et al 1997). Consistent with this, patients affected by Duchenne type neuromuscular dystrophy exhibit increased plasma levels of some muscle fiber content, including enzymes (McMillan et al 2011) and growth factors (D'Amore et al 1994). Of note with respect to our findings, it has been reported that patients affected by painful neuromuscular diseases such as polymyositis and Duchenne type neuromuscular dystrophy exhibit increased expression of GDNF in regenerating muscle fibers (Suzuki et al 1998a).…”
Section: Fig 2 Gdnf Produces Mechanical Hyperalgesia and Sensitizesmentioning
confidence: 61%
“…Although very large elevations in serum ALT are generally believed to be liver‐specific, ALT elevations are also noted following strenuous exercise and in patients with muscle diseases such as muscular dystrophy . A biomarker with greater liver specificity could be valuable in the clinic when the source of an ALT elevation is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated serum biomarkers, such as CK and alanine transaminase (ALT), are hallmarks of dystrophic muscle and are often used to diagnose the severity of muscle disease in both humans and mice (23,(42)(43)(44). We next measured the levels of serum CK in adult WT, Tg(Cmk-Mir486), Dmd mdx-5Cv , and Dmd mdx-5Cv Tg(Cmk-Mir486) mice.…”
Section: Mir-486 Is Enriched In Myogenic Tissues But Reduced In Dystrmentioning
confidence: 99%